Analysis of piping elbows in plane-bending using two different numerical models - Fonseca, E.M.M. (2010)
The piping systems are used in industrial plants subjected to any efforts. These components are constituted by straight and curved or elbow elements. Elbows attached to nozzle or straight pipes produce a stiffening effect due to the restraint of ovalization provided by the adjacent components. These elements have a small thickness and when submitted to any efforts, the excessive oval shape may reduce the structural resistance and can lead to structural collapse. The complexity of this analysis will need some powerful and efficient numerical techniques with high computing performance. This work presents the development of two different numerical models of a finite pipe element with two nodal sections for mechanical analysis. The formulation presented is based on shell displacement theory, where the displacement field is based in different polynomial functions or trigonometric functions, for rigid beam displacement, and based in development Fourier series to model warping and ovalization of pipe cross section, reported in Fonseca (2005), Thomson (1980) and Melo (1992). Finite elements models presented in this work have been compared with some numerical examples produced by other author (Thomas, 1981). Finally, some conclusions are presented about the efficiency of these finite pipe element models.